Introduction to Olga Derkachova, Children of War: Exploring the Trauma of War through Collective Creative Writing in Literary Workshops - Gardella, Lorrie Greenhouse (Group Work Around the Globe: Creating transformative connections in challenging times, 2018)
Proceedings of the XXXVIII and XXXIX International Symposium of the International Association for Social Work with Groups, New York City, New York, USA, June 15-18, 2016 and June 7-10 2017
Keywords: dept.swk